IDENTIFIKASI UJI FORMALIN PADA MIE BASAH MENGUNAKAN EKSTRAK UBI JALAR UNGU (Ipomoea batatas L.) DI PASAR TRADISIONAL DESA NIRU MUARA ENIM - Rahmi Garmini (Jurnal Delima Harapan, 2021)
The use of chemical additives, especially formaldehyde in food, needs to be watched out for together, both by producers and consumers. The use of formaldehyde in food is not allowed because it can cause poisoning in the human body. The purpose of this study was to describe the use of anthocyanin extract of purple sweet potato (Ipomoea batatas L.) as a natural indicator for formalin detection. The method used is experimental design. The results of this study can be seen that purple sweet potato contains anthocyanins which can be an indicator material for formalin which is acidic, this can be seen from the change in the color of the anthocyanin extract which changes when reacted with formalin, and seen from the purple sweet potato extract it turns reddish blue.